2006
DOI: 10.1063/1.2170144
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime-limiting defects in n− 4H-SiC epilayers

Abstract: Low-injection minority carrier lifetimes ͑MCLs͒ and deep trap spectra have been investigated in n − 4H-SiC epilayers of varying layer thicknesses, in order to enable the separation of bulk lifetimes from surface recombination effects. From the linear dependence of the inverse bulk MCL on the concentration of Z1/Z2 defects and from the behavior of the deep trap spectra in 4H-SiC p-i-n diodes under forward bias, we conclude that it is Z1/Z2 alone that controls the MCL in this material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
138
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(147 citation statements)
references
References 12 publications
6
138
0
3
Order By: Relevance
“…This measured carrier lifetime in as-grown 3C-SiC is much higher than the reported values in 3C-SiC grown by other methods, [19][20][21] even a little bit higher than the typical values in as-grown 4H-SiC. [11][12][13][14][15] The maximum carrier lifetime reported in asgrown 4H-SiC is 8.6 ls, 11 which was measured by l-PCD in a high-quality 50 lm thick CVD epilayer under an injection of 5 Â 10 12 cm À2 . The measured conditions are quite similar to our measurements.…”
mentioning
confidence: 39%
See 1 more Smart Citation
“…This measured carrier lifetime in as-grown 3C-SiC is much higher than the reported values in 3C-SiC grown by other methods, [19][20][21] even a little bit higher than the typical values in as-grown 4H-SiC. [11][12][13][14][15] The maximum carrier lifetime reported in asgrown 4H-SiC is 8.6 ls, 11 which was measured by l-PCD in a high-quality 50 lm thick CVD epilayer under an injection of 5 Â 10 12 cm À2 . The measured conditions are quite similar to our measurements.…”
mentioning
confidence: 39%
“…[11][12][13][14][15][16] The main lifetime-limiting defects are recognized as Z 1/2 and EH 6/7 centers, which are related to intrinsic defects with energy levels located at 0.65 eV and 1.55 eV below the conduction band, respectively. [11][12][13][14] Recently, it was shown that the reduction of the defects of Z 1/2 and EH 6/7 by post-growth processes results in an improvement of carrier lifetime. Kimoto et al 15 reported that the carrier lifetime in a 148-lm-thick 4H-SiC layer is enhanced from 0.69 to 9.5 ls after thermal treatment.…”
mentioning
confidence: 99%
“…However, with decreasing epi-layer thickness, the effective lifetime becomes limited by thickness and surface recombination, thereby losing sensitivity to epi-layer defects. 17 In the QUAD method, the surface depletion region is active in probing the defects; therefore QUAD is effective also in thin epi-layers. Such distinctly different behavior is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] These properties make SiC a suitable semiconductor for fabrication of devices that can operate at high power, high frequency and high temperatures. 2,3 Additionally, SiC is also a radiation hard material and this makes it a suitable semiconductor for devices that can operate both in high radiation environments and at high temperatures.…”
Section: Introductionmentioning
confidence: 99%